Architecting a Bias‐Free Photoelectrochemical CO2 Reduction System for Sustainable Formic Acid - Yinchao Yao; Zilong Wu; Zhiwei Zhao; Zhiyi Sun; Tiesong Li; Zebiao Li; Xinxin Lu; Zhuo Chen (Advanced Science)
Abstract Solar‐driven photoelectrochemical CO2 reduction represents a promising approach for the production of renewable liquid fuel but is limited by low photocurrent, the need for an external bias, and low carbon efficiency. This work employs a TiO2‐CdS/Se‐ZnSe/S photoanode to drive the sulfur oxidation reaction, achieving a photocurrent density of 12.7 mAcm−2 under AM 1.5G illumination and with an 87% retention after 100 h of continuous operation. Furthermore, through tailoring the adsorption capability for the *OCHO intermediate, the Cu6Sn5 catalyst exhibits a Faradaic efficiency of 92.8% for formic acid at −1.15 V in acidic media and maintains stability above 90% during a 120‐h test. Finally, the constructed system achieves bias‐free photoelectrochemical CO2 reduction to HCOOH and delivers a yield of up to 172.9 µmolh−1cm−2 over an 85‐h long‐term test, outperforming conventional solar‐driven systems. These findings highlight a cost‐effective strategy for solar‐driven liquid fuel production and provide valuable design concepts and insights into the development of photoelectrochemical systems.